Scope and significance of biotechnological improvement of tea - Tapan Kumar Mondal, Mainaak Mukhopdhayay, Akan Das (Journal of Plantation Crops, 2017)
Tea is an important plantation crop of India, which generates huge employment opportunities in rural and hilly backward places. Being a woody perennial crop with an economic life span of more than 60 years, it also has a role in sustaining the ecosystem. Because of its long gestation period, as observed from conventional breeding, alternative methods such as molecular breeding is highly relevant, which is rather limited in tea breeding programmes. Therefore, adoption of biotechnological approaches is a better option to shorten the breeding cycle of tea. Recent developments from the biotechnological research works on tea and related species are summarized in the review.